Serious game como ferramenta de ensino-aprendizagem na educação superior de enfermagem: revisão sistemática e desenvolvimento de protótipo - Fonseca, Rebeca Galvão (2019)
Advances in technology have influenced new parameters for contemporary society and it’s not different in the educational area especially regarding the methodological strategies used in higher education. In the Nursing field, the need to prepare properly trained and qualified nurses has been collaborating with the creation and use of educational games as a learning teaching tool. Serious games enable the construction of knowledge and also the training of activities by simulating various practices in a safe environment for the learner and patient; offering learning opportunities and behavioral changes. Ove to this, this study has as an objective to identify in the literature, evidence on the impact of the use of serious game as a teaching-learning tool for nursing academics and to present a tool for the teaching-learning process about the Nursing Process. This is a methodological and descriptive research, involving technological production, conducted from March 2017 to July 2019. A systematic review was conducted according to the recommendations of the PRISMA initiative and had the following guiding question: “What are the impacts on the use of serious games as an educational strategy tool in a higher education teaching in the Nursing course?”. The search was performed in eight databases (CINAHL, COCHRANE, ERIC, Embase, LILACS, Pubmed, Scopus and Web of Science) using terms defined from MeSH queries. After the manual selection, screening and evaluation steps for the selection of articles, sixteen composed the sample of this research. Among the main results stand out the positive aspects regarding the player's assessment of their learning, satisfaction with the tool used and contributions of the game in relation to the acceptance of the worked content, however, the need for further studies in this area was highlighted. The literature review was essential for a collaborative multidisciplinary team to develop a serious game based on the following steps: scope definition (pedagogical content), definition of game format and functionalities, script description and communication with the team development, prototyping with evaluation and production. As a result, the prototype serious game, type-RPG, single player mode, was titled “ProNurse Care”; whose purpose is based on the application of the Nursing Process focused on the individuality and needs of a fictitious patient. In the game, the user collects the medical history, anamnesis and physical examination, formulates nursing diagnoses and plans the results / goals and interventions. The feedback of the actions was inserted immediately and with each step successfully completed the player becomes able to proceed to the next step. After completion, the software was registered with the National Institute of Industrial Property (INPI), obtaining a favorable report under No. 512019000576-7. It is concluded that “ProNurse Care” is a promising tool to be used as a teaching tool of the Nursing Process; By being innovative and up-to-date it tends to become a motivating, effective and valid strategy that values patient safety and enhances student skills. However, before its implementation, it is intended to subject the tool to validation by experts, in order to subsidize the changes and enhancements to the final version of the game.